PERBEDAAN KOMUNIKASI BAHASA ANTARA ANAK USIA 9-10 TAHUN YANG DIASUH ORANG TUA DAN ANAK YANG DIASUH SAUDARA DI KAMPUNG PERS. BLANGKEDE KECAMATAN TERANGUN KABUPATEN GAYO LUES - Alsabarni (Lembaga Pengembangan Kinerja Dosen, 2021)
Children in the 9-10 age range are generally able to read well, and their communication skills are also starting to improve. The age range of 9-10 children is a transitional period from child to teenager and the role of parents is very important in building communication. This study aims to describe language communication between children aged 9-10 years who are cared for by parents and children who are cared for by relatives, and to describe the differences in language communication between children aged 9-10 years who are cared for by parents and children who are cared for by relatives in Pers Village. Blangkede, Terangun District, Gayo Lues Regency. Descriptive qualitative research using a case study strategy is in line with research on describing language communication in children aged 9-10. The ability of children in the Press Village. Blangkede, Terangun District, Gayo Lues Regency which has appropriate and structured language communication educated by parents is higher than the language communication of children aged 9-10 years who are educated by siblings, namely compared to 15 sentences and 12 sentences. Submission of children's language is more effectively channeled from parenting styles than other people's/relatives' parenting styles.